A Metastudy of Adultspan Journal: An Analysis of Publication Characteristics From 1999 to 2019. Issue 1 (3rd April 2021) - Rippeto, Margaret; Stewart, Elizabeth; Chowning, Michelle; Karkhanis, Sailee; Erford, Bradley T.; Kepley, Leah
Abstract : Articles published in Adultspan Journal from 1999 to 2019 were analyzed for trends over time in author characteristics (e.g., leading contributors and institutions, work setting, gender, domicile) and article characteristics (e.g., reporting standards, topics, research design, participant characteristics, and statistical sophistication).